A comparative study of opinions concerning faculty teaching behavior among faculty members and senior teachers training students in six teachers colleges in Bangkok, Thailand - 274814 Prakit Bhulapatna (Texas : North Texas State University, 1984)
Thesis (Ph.D) - North Texas State University, 1984